ANALISIS KOMPARATIF TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KARET DESA SUNGAI JALAU DENGAN DESA TERATAK KABUPATEN KAMPAR - Yusmini Yusmini; Shorea Khaswarina; Evy Maharani (Universitas Sebelas Maret, 2014)
This study aims to analyze the rubber farm income and household welfare level comparison of farmers in Desa Sungai Jalau and Desa Teratak. The results showed net income and labor income off arm families during the one-year analysis of rubber, a rubber farmer Desa Sungai Jalau net income of Rp11,253,051.5/ha and labor income families Rp17,833,933.8/ha, while the net income per farmer Desa Teratak year amounted to USD11,316,228.1/ha and labor income families Rp18,352,591.7/ha, net income and income of farming families working rubber farmer Desa Teratak is greater than Desa Sungai Jalau respectively 0.56% and 2.91%. The average of rubber farmers in Desa Sungai Jalau and Desa Teratak is welfare, based on the test there were significant differences in the level of well-being that significant in the community Desa Sungai Jalau with Desa Teratak.